1975
DOI: 10.1007/bf01944632
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone promotes dominance behavior and ovarian development in social wasps (Polistes annularis)

Abstract: Repeated topical application of juvenile hormone to workers of the primitive social wasp, Polistes annularis resulted in a disruption of colony social structure as indicated by a sharp increase in the frequency of dominance interactions. Ovarian maturation was also observed, probably as both a direct and an indirect effect of hormone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 5 publications
2
22
0
3
Order By: Relevance
“…While in many insect species JH functions in the adult as a gonadotropin, in some highly eusocial insects its role has shifted to regulate social behavior (Barth et al, 1975;Hartfelder and Engels, 1998;Bloch et al, 2000b;Hartfelder, 2000;Giray et al, 2005;Amsalem et al, 2014). In bumble bees, which are considered to be primitively eusocial (Michener, 1974), JH seemed to retain its role in reproduction but was also suggested to mediate aggression and Aggressive behavior was measured in individual bees kept in three-worker groups that were assigned to one of the following treatments: untreated control groups (n=12 groups), fed with 3 mg precocene-I diluted in sugar water (n=14 groups), fed with 3 mg precocene-I and treated with a topical application of 5 μl DMF (n=14 groups), or fed with 3 mg precocene-I and treated with a topical application of 100 μg JH-III diluted in 5 μl DMF (n=11 groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in many insect species JH functions in the adult as a gonadotropin, in some highly eusocial insects its role has shifted to regulate social behavior (Barth et al, 1975;Hartfelder and Engels, 1998;Bloch et al, 2000b;Hartfelder, 2000;Giray et al, 2005;Amsalem et al, 2014). In bumble bees, which are considered to be primitively eusocial (Michener, 1974), JH seemed to retain its role in reproduction but was also suggested to mediate aggression and Aggressive behavior was measured in individual bees kept in three-worker groups that were assigned to one of the following treatments: untreated control groups (n=12 groups), fed with 3 mg precocene-I diluted in sugar water (n=14 groups), fed with 3 mg precocene-I and treated with a topical application of 5 μl DMF (n=14 groups), or fed with 3 mg precocene-I and treated with a topical application of 100 μg JH-III diluted in 5 μl DMF (n=11 groups).…”
Section: Discussionmentioning
confidence: 99%
“…In pre-adult stages it regulates developmental processes and metamorphosis, while in adult females it induces vitellogenesis (the production of the major yolk protein) and reproduction (Nijhout and Wheeler, 1982;Robinson and Vargo, 1997;Hartfelder, 2000). In social insects, the hormone has acquired new roles such as regulating aggression and dominance in females of primitively eusocial insects such as bumble bees and wasps, regulating polymorphism and caste determination in isopteran and hymenopteran species, and regulating division of labor and behavioral maturation in the honey bee (Barth et al, 1975;Hartfelder and Engels, 1998;Bloch et al, 2000b;Hartfelder, 2000;Giray et al, 2005;Amsalem et al, 2014). Thus, the functions of JH were hypothesized to have changed during the transition from solitary to social lifestyles in insects.…”
Section: Introductionmentioning
confidence: 99%
“…Little work has been done on the endocrine correlates of queen dominance over workers in Polistes. In the one study published to date, Barth et al (1975) found that topical treatment of P. annularis workers with JH-III resulted in increased ovary development in workers and elevated levels of dominance behavior.…”
Section: Polistes Waspsmentioning
confidence: 97%
“…Em trabalhos realizados por Barth et al (1975) com P. annularis (Linnaeus, 1763), Röseler et al (1980Röseler et al ( , 1985 e Turillazzi et al (1982) com P. dominulus (Christ, 1791 relatam que altas taxas de hormônio juvenil estão relacionadas com o domínio e o maior desenvolvimento ovariano das fêmeas, e segundo Röseler (1991) as fêmeas com maior capacidade reprodutiva possuem ovários mais desenvolvidos e freqüentemente tornam-se rainhas em suas colônias.…”
Section: Resumo Divisão De Trabalho Em Colônias Da Vespa Social Neotunclassified